Synthesis and study of cell-penetrating peptide- modified gold nanoparticles (2018)
ABSTRAC: Background: In nanomedicine, gold nanoparticles (AuNPs) have demonstrated versatile therapeutic efficiencies and, in particular, have been developed for the treatment of various cancers due to their high selectivity in killing cancer, not healthy, cells. Methods: In this study, AuNPs were conjugated with the cell-penetrating peptide Cys-(Arg)8 Asp-Ser (CRRRRRRRRGDS) by direct cross-linking of the cysteine’s thiol group to the gold surface and a fibronectin-derived RGD group was also used due to its efficacy toward cancer cell targeting and possible promotion of healthy fibroblast functions. Results: Ultraviolet–visible absorbance spectrum and transmission electron microscope images of the synthesized peptide-capped AuNPs (PEP-AuNPs) validated the formation of AuNP aggregates. The presence of peptides on AuNPs was confirmed by Fourier transform infrared spectroscopy and quantified by a bicinchoninic acid assay. After being modified with the arginine-rich peptide, the AuNPs possessed a positive charge, as their zeta potential increased from -23.81±8.43 mV to 8 mV on average. In this manner, an easy method to conjugate AuNPs was shown here. Further, MTS assays were performed using healthy human dermal fibroblasts. After 24 hours of treatment with PEP-AuNPs, the cell density increased dramatically to around 25,000 cells/cm2. Results further showed a very high half-maximal inhibitory concentration of 69.2 μM for the PEP-AuNPs (indicating low toxicity). Conclusion: The results showed for the first time the ability of PEP-AuNPs to promote human dermal fibroblast cell viability, which after further investigation, may show an ability to replace cancerous tissue with healthy soft tissue.